Prognostic Significance of Platelet Recovery in Myelodysplastic Syndromes With Severe Thrombocytopenia. (December 2018) - Tang, Yaqiong; Zhang, Xinyou; Han, Shiyu; Chu, Tiantian; Qi, Jiaqian; Wang, Hong; Tang, Xiaowen; Qiu, Huiying; Fu, Chengcheng; Ruan, Changgeng; Wu, Depei; Han, Yue
Severe thrombocytopenia is a serious condition that frequently arises in patients with myelodysplastic syndrome (MDS) and is associated with poor prognosis. Few studies have investigated the prognostic significance of platelet recovery in patients with MDS having thrombocytopenia. We retrospectively analyzed 117 patients with de novo MDS complicated with thrombocytopenia (platelet count [PLT] < 100 × 10 9 /L). Patients received decitabine treatment (schedule A) or decitabine followed by allogeneic hematopoietic stem cell transplantation (allo-HSCT; schedule B). Severe thrombocytopenia (PLT < 20 × 10 9 /L), identified in 31 (26.5%) patients, was associated with poor survival. The PLT increased significantly after decitabine treatment in the 2 groups. Patients with thrombocytopenia treated with schedule B showed a superior prognosis compared to those treated with schedule A. On analysis of overall survival by platelet response in patients with severe thrombocytopenia, a significant survival advantage was observed in patients who achieved a platelet response, who would further benefit from allo-HSCT following decitabine therapy. The results indicate a potentially favorable prognostic impact of platelet response achieved with decitabine. Patients with MDS having severe thrombocytopenia may benefit from the effective recovery of platelets and further allo-HSCT following decitabine therapy.